Comparative Study of DIEP and PAP Flaps in Breast Reconstruction: Reconstructive Outcomes and Fat Necrosis - Kim, Hyung Bae; Han, Seong John; Kim, Eon Key; Eom, Jin Sup; Han, Hyun Ho (Journal of Reconstructive Microsurgery, 2023)
Background This study compared the reconstructive outcomes and fat necrosis of the profunda artery perforator (PAP) flap with those of the deep inferior epigastric perforator (DIEP) flap.Methods Data on all DIEP and PAP flap breast reconstructions performed between 2018 and 2021 at Asan Medical Center were compared. The overall reconstructive outcomes and presence of fat necrosis were analyzed through ultrasound evaluation performed by a board-certified radiologist.Results The PAP (n = 43) and DIEP flaps (n = 99) were used to reconstruct 31 and 99 breasts, respectively. The average age of the patients in the PAP flap group (39.1 ± 7.3 years) was lower than in the DIEP flap group (47.4 ± 7.7 years), and the body mass index (BMI) of patients undergoing PAP flap reconstruction (22.7 ± 2.8 kg/m2) was lower than those undergoing DIEP flap reconstruction (24.3 ± 3.4 kg/m2). There was no total loss of both flaps. Donor site morbidity was higher in the PAP flap group (11.1%) compared with the DIEP flap (1.0%). The rate of fat necrosis was higher in the PAP flaps (40.7%) than in the DIEP flaps (17.8%) during ultrasound.Conclusion In our study, we found that PAP flap reconstruction tended to be performed in patients who were younger with lower BMIs compared with the DIEP flap. Successful reconstructive outcomes were observed in both the PAP and DIEP flaps; however, a higher rate of necrosis was observed in the PAP flap compared with the DIEP flap.
Keywords: profunda artery perforator flap; deep inferior epigastric artery perforator flap; fat necrosis